Review of the Rising and Attaching Movement at Subdistrict of Kemang, Parung and Ciseeng in Bogor District - Fauzi, Ahmad; Murtedjo, Tedy; Chayati, Nurul (Universitas Ibn Khaldun Bogor, 2022)
The average level of vehicle ownership, number of students, working population, number of schools and the average family income can cause an increase in movement in the form of generation and attraction. The rise and pull of traffic on land use, especially in the Districts of Kemang, Parung and Ciseeng is one of the problems that often causes traffic jams during busy times in the morning and afternoon. To overcome these problems, the author opens an analysis of the generation and pull of the movement of traffic flow. The land use that will be analyzed to predict trip generation and attraction, namely the Hospital, Housing, Shopping Center, Office, Industry and Education Areas (SD, SMP and SMA/SMK/Private and Non-Private), while the classification of roads used are Arterial and Collectors located in Parung Subdistrict, Kemang Subdistrict and Ciseeng Subdistrict. Analysis of roads using 2017 MKJI and prediction of generation with ITE (Trip Generation Manual) and modeling with Saturn applications. Looking at the Existing Conditions at the study site for road network data, it can be concluded that the level of service at each entrance in the categories C and D, which means the value of C is a stable current and D is an unstable starting flow. The large number of trip generation and attraction at the study sites in three sub-districts namely Ciseeng, Parung and Kemang Subdistricts which included the education area, trading center or market, parks, and hospitals had a generation of 9,140 trip/hour and a Tug of 29,404 trip/hour. The design equation for transportation modeling in Ciseeng sub-district, Parung dang Kemang is Y = 94,565 + 1,015 (X).